2020
DOI: 10.1002/uog.21883
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of single‐gene defects to congenital cardiac left‐sided lesions in the prenatal setting

Abstract: Objectives To explore the contribution of single‐gene defects to the genetic cause of cardiac left‐sided lesions (LSLs), and to evaluate the incremental diagnostic yield of whole‐exome sequencing (WES) for single‐gene defects in fetuses with LSLs without aneuploidy or a pathogenic copy‐number variant (pCNV). Methods Between 10 April 2015 and 30 October 2018, we recruited 80 pregnant women diagnosed with a LSL who had termination of pregnancy and genetic testing. Eligible LSLs were aortic valve atresia or steno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
50
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 24 publications
(30 reference statements)
1
50
2
Order By: Relevance
“…Recent study by Sun et al specialized on prenatal cardiac leftsided lesions revealed diagnostic variants in 19.7% (13/66) cases, and found that KMT2D mutation occurred in 10.6% (7/66) of cases. 17 However, in this study, the diagnostic yield in left heart defect subgroup was relatively low (7.9%, 3/38). Only one fetus with a de novo truncating mutation in KMT2D gene was identified, presenting mitral atresia and absence of aortic valve.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Recent study by Sun et al specialized on prenatal cardiac leftsided lesions revealed diagnostic variants in 19.7% (13/66) cases, and found that KMT2D mutation occurred in 10.6% (7/66) of cases. 17 However, in this study, the diagnostic yield in left heart defect subgroup was relatively low (7.9%, 3/38). Only one fetus with a de novo truncating mutation in KMT2D gene was identified, presenting mitral atresia and absence of aortic valve.…”
Section: Discussioncontrasting
confidence: 56%
“…In the study of Sun et al, only fetuses with cardiac leftsided lesions leading to termination of pregnancy were recruited which could represent more severe phenotypes, and 60% cases were hypoplastic left heart syndrome (HLHS). 17 While in our study, 78.9%…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…New approaches such as NGS can provided CHD genetic etiology. 25 Our study indicates the first novel de novo germline mutation identified by WES in an Iranian family with different types of CHD. Although we surveyed nine likely pathogenic variants in the family members but none of them were completely segregated except one, c.T6797C in the NOTCH1 gene, and this illustrates the complexity of the CHD causing identification.…”
Section: Discussionmentioning
confidence: 64%